Arctic Ocean Surface Energy Flux and the Cold Halocline in Future Climate Projections. Issue 2 (11th February 2020) - Metzner, Enrico P.; Salzmann, Marc; Gerdes, Rüdiger
Abstract: Ocean heat transport is often thought to play a secondary role for Arctic surface warming in part because warm water which flows northward is prevented from reaching the surface by a cold and stable halocline layer. However, recent observations in various regions indicate that occasionally, warm water is found directly below the surface mixed layer. Here we investigate Arctic Ocean surface energy fluxes and the cold halocline layer in climate model simulations from the Coupled Model Intercomparison Project Phase 5. An ensemble of 15 models shows decreased sea ice formation and increased ocean energy release during fall, winter, and spring for a high‐emission future scenario. Along the main pathways for warm water advection, this increased energy release is not locally balanced by increased Arctic Ocean energy uptake in summer. Because during Arctic winter, the ocean mixed layer is mainly heated from below, we analyze changes of the cold halocline layer in the monthly mean Coupled Model Intercomparison Project Phase 5 data. Fresh water acts to stabilize the upper ocean as expected based on previous studies. We find that in spite of this stabilizing effect, periods in which warm water is found directly or almost directly below the mixed layer and which occur mainly in winter and spring become more frequent in high‐emission future scenario simulations, especially along the main pathways for warm water advection. This could reduce sea ice formation and surface albedo. Plain Language Summary: Under the ocean surface, warm water flows from the Atlantic Ocean to the Arctic Ocean. But often it is prevented from reaching the surface by a less salty, and therefore lighter, cold water layer above the warm water. However, recent observations have shown that this cold layer can at times disappear. As long as the warm water from the south stays below this cold and stable layer, warmer ocean currents in a warmer climate might not contribute much to Arctic surface warming. In this study we look at output data from climate models. We find that in a future climate scenario more energy is released from the ocean to the atmosphere, especially in winter. Because in winter the upper meters of the ocean cool down quickly, this energy must come from deeper ocean layers. We find that events in which warm water is not far from the surface occur more often in the future climate simulations than in either past or present‐day simulations. This could reduce sea ice formation and surface albedo. Key Points: Climate models show increasing Arctic Ocean energy release through the surface in winter and spring Sharp temperature gradients below the surface mixed layer facilitate this increased energy release Warm water from below increasingly reaches the surface mixed layer in future climate projections